Impact of Lockdown in India: A Case Study Comparing Kanataka with International Model - Sebastian, Stelvin; Paul, Aby; Joseph, Jeeva; Joby, Joel; Saijan, Sanjo; Vilapurathu, Jobin Kunjumon (Kesmas, 2020)
The COVID-19 was declared a pandemic and a global health emergency by WHO, prompting various countries to implement early and stringent social distancing protocols through lockdown, to flatten the epidemic curve. The objective of the present study was to assess the impacts and effectiveness of the lockdown protocol in Karnataka and Punjab, compared with the implementation of this method in Australia and the UK. This study involved the collection of data from different authorized databases, in two phases. The first phase included the time starting with the first-reported index case through the 14th day after the declaration of lockdown, for each country. The second phase involved the data collected between the 15th day through the 28th day of the lockdown. The highest doubling rate for cases was observed in Australia, followed by Karnataka and Punjab, whereas the lowest was observed in the UK. Comparisons of the numbers of the samples tested, the mortality rate, and the recovery rate between Karnataka and Punjab, after the implementation of lockdown, revealed a better recovery rate and lower mortality rate in Karnataka than in Punjab. This study revealed that the implementation of social distancing and lockdown reduced the transmission of the coronavirus and the number of cases reported. However, the effectiveness of lockdown varied among locations, due to demographic and physiological differences.